2005
DOI: 10.1021/ma0500685
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry Driven Distribution of 1,4-Diaminocyclohexane Residues over the Crystalline and Amorphous Phase in Copolyamides 4.14/1,4-DACH.14. A Solid-State NMR and Temperature-Dependent WAXD Study

Abstract: Following our previous study on the stereoselective cocrystallization of linear and cyclic dicarboxylic acid residues in copolyamides 12.6/12.1,4-cyclohexanedicarboxylic acid (12.6/12.1,4-CHDA, Vanhaecht et al., Macromolecules 2004, 37, 421), we have now investigated a series of copolyamides containing trans or cis isomers of 1,4-diaminocyclohexane (1,4-DACH), viz. 4.14/1,4-DACH.14. Solidstate NMR studies and WAXD experiments demonstrate that the cis isomer is present in the amorphous regions of the copolyami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…However, surprisingly, it appears to have been scarcely used for polyHIPE analysis. ,, We investigated the chemical structure of the VT-MBA polyHIPE monoliths by MAS NMR spectroscopy (on sample P34VT4). In addition with the more common 1 H and 13 C MAS NMR analysis, 15 N MAS NMR spectra were also recorded as previously reported for polyamide and N-containing insoluble polymers. Experimental results displayed in Figure were in complete agreement with the expected structure: (i) 13 C NMR spectra displayed the two signals assigned to the quaternary carbons belonging to the triazole ring (150.7 and 143.1 ppm), two lines for methylene (52.5 ppm) and methine (38.1 ppm) aliphatic carbons of the main chain, and a well-defined small peak at 173 ppm attributed to the carbonyl groups from MBA. The corresponding integration represented roughly 4% of the integration of triazole ring carbons.…”
Section: Resultssupporting
confidence: 77%
“…However, surprisingly, it appears to have been scarcely used for polyHIPE analysis. ,, We investigated the chemical structure of the VT-MBA polyHIPE monoliths by MAS NMR spectroscopy (on sample P34VT4). In addition with the more common 1 H and 13 C MAS NMR analysis, 15 N MAS NMR spectra were also recorded as previously reported for polyamide and N-containing insoluble polymers. Experimental results displayed in Figure were in complete agreement with the expected structure: (i) 13 C NMR spectra displayed the two signals assigned to the quaternary carbons belonging to the triazole ring (150.7 and 143.1 ppm), two lines for methylene (52.5 ppm) and methine (38.1 ppm) aliphatic carbons of the main chain, and a well-defined small peak at 173 ppm attributed to the carbonyl groups from MBA. The corresponding integration represented roughly 4% of the integration of triazole ring carbons.…”
Section: Resultssupporting
confidence: 77%
“…These included comonomer units can greatly influence their Brill transition behaviors. For instance, Koning and co-workers found that incorporation of trans cyclic comonomers into polyamides inhibited the trans – gauche conformational evolution, and thus the α phase was maintained during heating. In other cases, incorporating diaminoisoidide in aliphatic copolyamides caused conformational disorder and resulted in large amounts of gauche bonds, facilitating the formation of a γ phase. These studies show a possible influence of comonomer inclusion on the trans / gauche conformational evolution, thus affecting the α/γ Brill transition of copolyamides. Nevertheless, an accurate conclusion about how the existence of comonomer units (i.e., the comonomer defects) in the crystalline phase affects the Brill transition behavior of copolyamides is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, cocrystallization can occur in PA-based copolymers with a stereochemical comonomer. Koning et al reported one non-classical Brill transition with a crossing rather than a merging of the two reflections of the α-phase in the copolyamides in the presence of trans cycloaliphatic residues in the crystalline phase. , They believed that the crossing behavior is caused by the reduced mobility of the chains, preventing the formation of the pseudohexagonal phase before the melting temperature . Based on the literature, the observed differences between PA1012 and PAE38 samples in Figure are probably caused by the accelerated mobility contributed by the PTMO SS.…”
Section: Resultsmentioning
confidence: 99%
“…29,69 They believed that the crossing behavior is caused by the reduced mobility of the chains, preventing the formation of the pseudohexagonal phase before the melting temperature. 69 Based on the literature, the observed differences between PA1012 and PAE38 samples in Figure 7 are probably caused by the accelerated mobility contributed by the PTMO SS.…”
Section: ■ Introductionmentioning
confidence: 99%